Do Capital Structure, Retakaful, and Loss Ratio affect to Syariah Insurance Liquidity? - Alfiya Putri; Falikhatun Falikhatun (ITB AAS INDONESIA Surakarta, 2023)
Syariah Insurance has an important role in mitigating the risk of Islamic banking so that Islamic banks can quickly recover from the problems they face, while Islamic banking facilitates Islamic insurance in its transactions so that it is more accessible to the public. This paper aims to dig deeper into the influence of capital structure, retakaful, and loss ratio on the liquidity ratio of Islamic insurance. Using panel data from 24 companies from 2013 to 2019, this study uses the Hausman test to distinguish between fixed and random effects. The Cash Ratio is used as a proxy for the liquidity ratio. The sample of sharia insurance companies is from OIC countries such as Indonesia, Malaysia, UAE, Pakistan, Bangladesh. Our findings reveal that statistically there is a significant influence between capital structure, retakaful, and the loss ratio on the liquidity ratio. Partially, capital structure has a negative effect, while retakaful and loss ratios have no effect on sharia insurance liquidity in OIC member countries